Clinical outcomes after primary prevention defibrillator implantation are better predicted when the left ventricular ejection fraction is assessed by cardiovascular magnetic resonance - Laure Champ-Rigot; Pauline Gay; Frédéric Seita; Leila Benouda; Remy Morello; Arnaud Pellissier; Joachim Alexandre; Eric Saloux; Paul Milliez (Journal of Cardiovascular Magnetic Resonance, 2020)
Abstract Background The left ventricular ejection fraction (LVEF) is the key selection criterion for an implanted cardioverter defibrillator (ICD) in primary prevention of sudden cardiac death. LVEF is usually assessed by two-dimensional echocardiography, but cardiovascular magnetic resonance (CMR) imaging is increasingly used. The aim of our study was to evaluate whether LVEF assessment using CMR imaging (CMR-LVEF) or two-dimensional echocardiography (2D echo-LVEF) may predict differently the occurrence of clinical outcomes. Methods In this retrospective study, we reviewed patients referred for primary prevention ICD implantation to Caen University Hospital from 2005 to 2014. We included 173 patients with either ischemic (n = 120) or dilated cardiomyopathy (n = 53) and who had undergone pre-ICD CMR imaging. The primary composite end point was the time to death from any cause or first appropriate device therapy. Results The mean CMR-LVEF was significantly lower than the mean 2D echo-LVEF (24% ± 6 vs 28% ± 6, respectively; p < 0.001). CMR-LVEF was a better independent predictive factor for the occurrence of the primary composite endpoint with a cut-off value of 22% (Hazard Ratio [HR] = 2.22; 95% CI [1.34–3.69]; p = 0.002) than 2D echo-LVEF with a cut-off value of 26% (HR = 1.61; 95% CI [0.99–2.61]; p = 0.056). Combination of the presence of scar with CMR-LVEF< 22% improved the predictive value for the occurrence of the primary outcome (HR = 2.58; 95% CI [1.54–4.30]; p < 0.001). The overall survival was higher among patients with CMR-LVEF≥22% than among patients with CMR-LVEF< 22% (p = 0.026), whereas 2D echo-LVEF was not associated with death. Conclusions CMR-LVEF is better associated with clinical outcomes than 2D echo-LVEF in primary prevention using an ICD. Scar identification further improved the outcome prediction. The combination of CMR imaging and echocardiography should be encouraged in addition to other risk markers to better select patients.